Implementation of a problem-based learning model assisted with student worksheets to improve mathematical reasoning skill for students of grade X SMK - Azzahrah, Astriani; Putra, Harry Dwi; Habibullah, Habibullah (CV. Pustaka Literasi Ilmiah, 2023)
This study aims to analyze application problem based learning assited by student worksheets to improve the mathematical reasoning skill of class X Vocational High School students in the matter of a system of two-variable linear equations for the 2022/2023 Academic Year. The research method used is pre-experimental design. The subjects of this study were 35 studens of class at a SMK in Cimahi City. Research data was collected using tests and questionnaires. The data collection technique used in this study was in the form of the test instruments in the form of pretest and posttest as well as questionnaires to analyze student responses. The results of the research show 1) the application of the problem based learning can improve students’ mathematical reasoning skill, this is show from the average score N-Gain student size are in the high criteria, where as many as 11 students with the category N-Gain medium and 24 students are in the category N-Gain tall, 2) student responses are in the category of strongly agree, meaning that students strongly agree with the application of the learning problem-based learning which can improve mathematical reasoning ability.